2001
DOI: 10.1159/000052786
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Reserve for Cerebral Vasomotor Response to <i>L</i>-Arginine in the Elderly: Evaluation by Transcranial Doppler Sonography

Abstract: Background: Nitric oxide is pivotal in endothelially dependent vasodilatory regulation. An association of endothelial dysfunction with aging has been documented in the forearm and coronary vascular beds. However, the influence of aging in the human cerebral circulation, where regulation is particularly complex, is incompletely understood. Objective: We systematically administered L-arginine, a precursor of nitric oxide, to evaluate the influence of aging on nitric oxide-mediated cerebral vasomotor regulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 19 publications
1
39
1
1
Order By: Relevance
“…On intravenous infusion of L-arginine, cerebral blood flow velocity increased and mean blood pressure decreased in healthy volunteers; however, the hypotensive effect did not differ between older (average age 70.2 years) and younger (28.8 years) groups. The cerebral circulation in the older group showed a blunted, smaller, and more easily saturated vasomotor response compared with that in the younger group (Okamoto et al, 2001). NO may be involved in the increased cerebral blood flow velocity.…”
Section: Studies On Humansmentioning
confidence: 76%
“…On intravenous infusion of L-arginine, cerebral blood flow velocity increased and mean blood pressure decreased in healthy volunteers; however, the hypotensive effect did not differ between older (average age 70.2 years) and younger (28.8 years) groups. The cerebral circulation in the older group showed a blunted, smaller, and more easily saturated vasomotor response compared with that in the younger group (Okamoto et al, 2001). NO may be involved in the increased cerebral blood flow velocity.…”
Section: Studies On Humansmentioning
confidence: 76%
“…Diminished cVMR is reported in normal aging 3,6,23 and in individuals with a variety of vascular-related disease conditions. 24 -28 It exhibits diurnal variations, reaching low points during morning hours when stroke events are most prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 Although these observations would seem to suggest l-arginine supplementation as a therapeutic strategy, several studies have shown that l-arginine reactivity varies depending on time point after injury, vascular bed, and species studied, age, and the underlying disease. [48][49][50][51][52][53] One of the limitations of our study is that we focused on a specific time point after injury. Additional studies are needed to address the longitudinal course of vascular responses including earlier times after TBI and later time points after clinical recovery.…”
Section: Fig 7 Total Arginase Activity Is Increased After Traumaticmentioning
confidence: 99%